Pharmacist-led interventions for vascular surgery patients: a prospective study on reducing drug-related problems - Slavka Porubcova; Kristina Szmicsekova; Kristina Lajtmanova; Veronika Slezakova; Michal Jakubik; Eva Drobna; Jan Tomka; Zuzana Kobliskova; Lucia Masarykova; Lubica Lehocka; Tomas Tesar (BMC Health Services Research)
Abstract Background Vascular surgery patients are at a high risk of polypharmacy and drug-related problems. Only a limited number of studies have explored the impact of hospital pharmacists being members of a multidisciplinary team in the care of vascular surgery patients. The clinical study (Trial Registration Number NCT04930302, 16th June 2021) aimed to assess the impact of pharmacist-led interventions on the prevalence of drug-related problems among patients hospitalised at the vascular surgery department. Methods The study, conducted at a specialised hospital in Slovakia during a 1-year period, included adult patients with carotid artery disease or lower extremity artery disease, taking ≥3 medications. Medication reconciliation and medication reviews were performed by hospital pharmacists at both admission and discharge. Pharmacist-proposed interventions were documented and communicated to the physician, patients were educated about their medications upon discharge. Results Among our study participants (n = 105), the average number of drug-related problems at admission was 2.3 ± 2.1, significantly decreasing to 1.6 ± 1.8 at discharge (p < 0.001). The predominant drug classes associated with drug-related problems were those related to the cardiovascular system (41.9%). At admission, the most frequent drug-related problem was untreated indication (40.3%), mostly caused by the failure to prescribe statin in patients with lower extremity artery disease. The highest acceptance rate of pharmacist-led interventions was at hospital admission (66.1%). More than 50% of patients were classified as those with good understanding of their pharmacotherapy. Conclusions This study demonstrates that pharmacist-led interventions significantly reduce drug-related problems in vascular surgery patients during hospitalisation, contributing to patient safety and clinical outcomes. Trial registration ClinicalTrials.gov Trial Registration Number: NCT04930302, 16th June 2021.